Corrigendum to "A tandem enol silane Formation-Mukaiyama aldol reaction mediated by TMSOTf" [Tetrahedron Lett. 48 (2007) 3559–3562]. Issue 13 (28th March 2018) - Downey, C. Wade; Johnson, Miles W.
Graphical abstract: Highlights: TMSOTf and Hunig's base promote aldol reactions of esters and aromatic ketones with aldehydes. Excess base relative to TMSOTf favors the β-silyloxy carbonyl product. Excess TMSOTf relative to base favors the α, β-unsaturated carbonyl product.